The use of the darnell techniques as a motivational element to promote creative writing in students of an efl class - Peralta, Andrés; Valencia, Guadalupe
This investigatory project had the purpose of proving if the motivational techniques developed by Miriam Darnell were efficient when applied during a lesson in a local high school. It is important to know that these techniques were originally developed for American students who were native speakers of English, so our challenge was to adapt them for an EFL classroom. The project was based on the design and application of a lesson in order to increment the disposition of students to write creatively in class, and the subsequent diagnosis and analysis of the data obtained. Besides the lesson plan, a previous research on the importance of creative writing and motivation in education, different approaches from additional authors and researchers, and the problems that EFL teachers must deal with in the classroom was done, so the needs thatthe students who participated in the application class could be satisfied. As a result,what we could perceive and how the students themselves felt about the way the class was carried outdemonstrated that these techniques proved indeed efficient at the time of motivating learners to write. This way we hoped to contribute in some way to the creative writing process of our students by adopting these techniques in our daily teaching practice.